Lineage analysis of human papillomavirus types 33 and 35 based on E6 gene in cervical samples from Tehran, Iran - Mohammad Shabanpour; Sima Taherkhani; Zabihollah Shoja; Mahtab Eftekhari; Somayeh Jalilvand (Scientific Reports)
Abstract Knowing the geographical distribution of lineages and sublineages of each HPV type is beneficial for the epidemiological and evolutionary studies of this virus. However, no studies have analyzed the variants of HPV 33 and 35 in Iranian women. To investigate the sequence variation of HPV 33 and 35 E6 gene, 42 and 92 samples were analyzed using nested PCR and sequencing, respectively. Sublineage analysis of HPV 33 showed that most of the samples belonged to the A2 sublineage (85.8%) and the remaining were classified to the A1 sublineage. Four mutations at positions A132C, A213C, A364C, and A480T were detected, among which two mutations A213C and A364C led to amino acid changes corresponding to positions K35N and N86H of amino acid, respectively, in 85.8% of samples. For HPV 35, two sublineages A1 and A2 were found in studied samples with a prevalence of 84.8 and 15.2%, respectively. Seven nucleotide changes were observed at positions of C127G/T, A130C, A131C, C136T, G249T, A326G, and C341T. Three of these mutations including A130C, G249T, and C341T resulted in amino acid changes at positions of E7D, C47F, and R78W in 4.4%, 3.3%, and 9.8% of samples, respectively. Concerning HPV 33 or 35 distinct lineages by histology/cytology status, no statistically significant differences were observed. Our results indicated that sublineages A2 of HPV 33 and A1 of HPV 35 were dominant in Tehran, Iran. However, more studies with larger sample sizes from different histopathological stages of cervix in various geographical regions of Iran are necessary to evaluate the pathogenicity risk of HPV 33 and 35 (sub)lineages in Iranian women with cervical cancer in the future.